Paradox of Modern Pregnancy: A Phenomenological Study of Women's Lived Experiences from Assisted Pregnancy. (3rd May 2015) - Ranjbar, Fahimeh; Akhondi, Mohammad-Mehdi; Borimnejad, Leili; Ghaffari, Saeed-Reza; Behboodi-Moghadam, Zahra
Abstract : The purpose of our study was describing the meaning of pregnancy through Assisted Reproductive Technologies (ARTs). A qualitative design with hermeneutic phenomenology approach was selected to carry out the research. Semistructured in-depth interviews were conducted with 12 women who experienced assisted pregnancy. Three themes emerged from women's experience including finding peace in life, paradoxical feelings, and struggling to realize a dream. We concluded that pregnancy is the beginning of a new and hard struggle for women with fertility problems. The findings of our study resulted in helpful implications for the health care professionals managing assisted pregnancies.